Earthen Stūpas of Pre-ancient Nepāl - Ranjitkar, Junu Basukala (Historical Journal, 2020)
The initial stūpas of pre-ancient Nepal were erected using earthen mounds. However, the Pāli and Sanskrit Buddhist texts do not mention that stūpas have to be earthen mounds. Only the Pāli Jātaka story Sujāta mentions the presence of earthen mound stupa containing the relics of a deceased person. The earthen mound stūpas were initially made in the Indian sub-continent after Buddha’s Mahāparinibbāna. There were ten preliminary stūpas that were erected containing the Buddha’s relics, a vessel and ashes. One of them, Rāmagrāma stūpa, is still in existence in its original form. When Emperor Asoka converted to Buddhism, he erected 84,000 stūpas with small relics of the Buddha, extracting those relics from the seven original stūpas. Not only that, he also went on to enlarge the size of a few original stūpas using bricks in the construction process. Piprahavā stūpa of Kapilvastu, Nibbāna stūpas of Kanakamuni and Krakuchhanda, twin stūpas of Dhamnihavā were renovated by enclosing the earthen mound with bricks. The Bhishvā stūpa of Birgunj and three stūpas of Pātan and a stūpa of kothuvahī are still in existence in their original form. However, all these stūpas are enclosed by walls built in the later part of the centuries to preserve them. The Chārumatī stūpa and the Yampi stūpa were built in Vajrayāna tradition. However, in recent times the infrastructure developments in the cities have led to the use of modern materials like cement and white plaster and altering even the architectural styles of some of the stupas. The north-east section of Chārumatī stūpa and the Yampi stūpa have suffered this impact.